2019
DOI: 10.1590/s1677-5538.ibju.2018.0730
|View full text |Cite
|
Sign up to set email alerts
|

Seminal citrate is superior to PSA for detecting clinically significant prostate cancer

Abstract: Purpose: To establish whether the citrate concentration in the seminal fl uid ([CI-TRATE]) measured by means of high-resolution nuclear magnetic resonance spectroscopy (1HNMRS) is superior to the serum prostate-specifi c antigen (PSA) concentration in detecting of clinically signifi cant prostate cancer (csPCa) in men with persistently elevated PSA. Materials and Methods: The group of patients consisted of 31 consecutively seen men with histological diagnosis of clinically localized csPCa. The control group co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…Its concentration is the primary factor affecting seminal pH and has been promoted as a biomarker of prostate function and prostate cancer. 17,18 Besides citrate, the levels of succinic acid and aconitic acid, TCA cycle intermediates, were significantly decreased in the ON and OA group in our study. In the seminal fluid, pyruvate is either secreted from seminal glands or generated by a catabolic process of fructose metabolism.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Its concentration is the primary factor affecting seminal pH and has been promoted as a biomarker of prostate function and prostate cancer. 17,18 Besides citrate, the levels of succinic acid and aconitic acid, TCA cycle intermediates, were significantly decreased in the ON and OA group in our study. In the seminal fluid, pyruvate is either secreted from seminal glands or generated by a catabolic process of fructose metabolism.…”
Section: Discussionsupporting
confidence: 49%
“…Citrate is the initial product of the tricarboxylic acid (TCA) cycle and is abundantly accumulated by glandular epithelial cells in the human prostate's peripheral region. Its concentration is the primary factor affecting seminal pH and has been promoted as a biomarker of prostate function and prostate cancer 17,18 . Besides citrate, the levels of succinic acid and aconitic acid, TCA cycle intermediates, were significantly decreased in the ON and OA group in our study.…”
Section: Discussionsupporting
confidence: 47%
“…phosphorylation to produce ATP, normal prostate epithelium depends on aerobic glycolysis with glucose and aspartate as the primary carbon donors (17). In malignant prostate tissues, ZIP1 expression and citrate production are decreased, while ACO2 expression is increased, converting prostate cells from citrateproducing to a citrate-oxidizing phenotype (18)(19)(20)(21)(22). These changes enhance the capacity for energy production to support proliferation and metastasis, and provide evidence that metabolic adaptation occurs in prostate cancer (Figure 2).…”
Section: Prostate Cancer Metabolismmentioning
confidence: 97%
“…Qin et al found that prostate cancer antigen 3 (PCA3) distinguishes healthy patients from patients with PCa; this biomarker is over--expressed in more than 95% of PCa cells. The influence of ethnicity on PCA3 is not clear; we need more studies to conclude differential diagnosis of PCa (9)(10)(11).…”
Section: Evidence Synthesis Molecular Basis For the Impact Of Lifesty...mentioning
confidence: 99%